Electrochemical genosensor for the detection of Dynophisis spp. dinoflagellates - Pereira, Eduarda Almeida Rufo (2023)
Harmful algal blooms (HABs) pose a significant threat to the environment and public health. To minimize their impact, it is necessary to develop technological devices towards their fast and precise detection. Therefore, the aim of this work was to develop an analytical approach based on an electrochemical genosensor device in order to create a low-cost platform to monitor the presence of dinoflagellates from the genus Dinophysis. The design of this deoxyribonucleic acid (DNA)-based sensor consists in three steps: (i) Sensing phase, where a mixed self-assembled monolayer composed by a linear DNA-capture probe and mercaptohexanol onto the electrode’s surface is generated; (ii) Hybridization of complementary DNA sequence through a “sandwich” hybridization assay; and (iii) Electrochemical detection by chronoamperometry, taking advantage of an enzymatic scheme to amplify the signal. The best analytical conditions were used to study the relationship between the electrochemical signal and the DNA-target concentration, to produce the best electrochemical genosensor device. Polymerase chain reaction (PCR) was used for validation of the electrochemical genosensor. These advancements contribute to the ongoing efforts in environment and public health’s protection by providing effective tools for mitigating the risks of HABs. Further research and implementation of these methods hold great potential in ensuring the safety and sustainability of aquatic ecosystems.